Trypanosoma congolense: Expression of a heat shock protein 70 and initial evaluation as a diagnostic antigen for bovine trypanosomosis - Boulange, A.F.; Katende, J.; Authié, Edith (Elsevier, 2002)
A 69-kDa immunodominant protein of Trypanosoma congolense was identified as a member of the hsp70 family that is homologous to mammalian BiP. We report here the expression of the gene encoding the T. congolense BiP in a bacterial system. Dot blotting of the truncated recombinant proteins confirmed that BiP antigenicity is mainly located in the C-terminal third of the molecule. A recombinant fragment corresponding to this region was used as an antigen in an indirect ELISA and an initial evaluation of its diagnostic potential for bovine trypanosomosis was performed. The test showed limited sensitivity for detection of primary-infected cattle but was capable of accurately detecting secondary infections. As BiP and its derivatives may be produced at low cost under stable forms allowing standardization of the tests, they warrant further evaluation as antigens fro serodiagnosis of bovine trypanosomosis.